Family Violence and Football: The Effect of Unexpected Emotional Cues on Violent Behavior - Card, David
We study the link between family violence and the emotional cues associated with wins and losses by local professional football teams. We hypothesize that the risk of violence is affected by the 'gain-loss' utility of game outcomes around a rationally expected reference point. Our empirical analysis uses police reports of violent incidents on Sundays during the professional football season. Controlling for the pre-game point spread and the size of the local viewing audience, we find that upset losses (defeats when the home team was predicted to win by 4 or more points) lead to a 10 percent increase in the rate of at-home violence by men against their wives and girlfriends. In contrast, losses when the game was expected to be close have small and insignificant effects. Upset wins (when the home team was predicted to lose) also have little impact on violence, consistent with asymmetry in the gain-loss utility function. The rise in violence after an upset loss is concentrated in a narrow time window near the end of the game, and is larger for more important games. We find no evidence for reference point updating based on the halftime score.reference dependence, gain-loss utility, intimate partner violence